PENGARUH GAYA KEPEMIMPINAN DAN BEBAN KERJA TERHADAP KEPUASAN KERJA - Suharjon, Nadira Salsabilla; Adi, Agung Nugroho (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The objective of this research is to identify the effects of leadership style and work load on the job satisfaction of employees working in the General Service Department of Bungo Regency Office. The population of this quantitative explanatory research consists of 98 people. Since census sampling was used, all of them were selected as the respondents. The research instruments were assessed using validity and reliability tests. The research data was evaluated through classical assumption consisting of normality, multicollinearity, and heteroscedasticity tests before being analyzed using multiple linear regression. The hypothesis testing was conducted using t test, F test, and coefficient of determination test. The results show that leadership style and work load significantly influence employee job satisfaction. Further, the adjusted R-squared value of 0.821 indicates that the effects of leadership style and work load on employee job satisfaction is 82.1%. Hence, the remaining 17.9% of the influence is explained by other variables other than leadership style and work load.